Access to justice: migrant domestic workers in Buenos Aires City - Jaramillo Fonnegra, Verónica (2019)
The Autonomous City of Buenos Aires is the Latin American city with the most migrant domestic work, mostly made by women. Although between 2003 and 2013 some regulations that improved labor and migratory rights were modified, regulatory changes have been slow to materialize. This is why that the purpose of this article is to expose the main obstacles that migrant domestic workers experienced at the time they tried to access labor justice in Argentina between 2011 and 2015, moments of legislative transition. Some of the main conclusions show that the way in which domestic work is carried out affects the possibilities of accessing justice; not only because of the private characteristic of the home in which the work is carried out, but also because the bond of affection between the employer and the worker is configured as a limit when it comes to demanding justice. Likewise, some material and symbolic obstacles are exposed here, such as the lack of time and money to claim rights. The methodology used is the activist ethnography, which mixes qualitative research-action techniques with documentary analysis, especially of normative ones.